Anthropological perspective on the adaptation of the activities of a health center to its physical and social setting: Virgen del Remedio Neighbourhood in Alicante - María Mercedes Rizo Baeza; Santiago Fernández Ardanaz (Universidad de Alicante, 2012)
The relationship of a health center with its habitat as an interactive element between people and their environment is described. Within this context, the objectives are: - Describing the habitat, the social and cultural characteristics and the relationship between people and their setting. - Studying aspects of the built setting which can influence quality of life of its inhabitants, not merely considered as health services users. - From this study, redefining the role of the health center as an interactive element to moderate and change that habitat, from an integral concept of health. The data collected from the field work were used to carry out the anthropological analysis of the neighborhood, focusing on the private space, the home, as an anthropological setting, and the public space, verifying a lack of "anthropological settings" as places where the individual global needs are met. This neighborhood is anthropologically a "place outside of and "transition place", causing excision and marking the "alien" trait in front of the rest of the city, besides not creating any communication system for the population within the neighborhood. In this state of things, the health center must become an anthropological meeting place and a means of access to social life that not only will allow people to recover their "identity" but also will create communication nets within the neighborhood. It is a service that "will unify everyone". For this purpose the following needs arise: - The staff must be permanent and has to know the anthropological characteristics of the population. The concept of family doctor and family nurse springs up again. - Activities must be adapted to the wider aspect of the definition of health, integrating individuals and environment. - Universality of the public health system, without extra costs or fees for the patient.